Comparison on losses and flux distribution between two of 3 phase distribution transformer core 3000 kVA assembled with different angle of T-Joint - Ismail, Daut; Dina Maizana, Maiz Ahmad; Shuhaimi, Zakaria; Soib, Taib (Malaysia - Japan University Center (MJUC), 2008)
Organized by Malaysia - Japan University Center (MJUC), 12th - 15th November 2007 at Kuala Lumpur, Malaysia.